Data and analytics in corporate real estate: Do you have the right talent? - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2015)
Is the lack of suitable data and analytics talent in your corporate real estate (CRE) team preventing you from contributing to the wider business strategy?